2017
DOI: 10.1177/1010428317729933
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells and differentiation therapy

Abstract: Cancer stem cells can generate tumors from only a small number of cells, whereas differentiated cancer cells cannot. The prominent feature of cancer stem cells is its ability to self-renew and differentiate into multiple types of cancer cells. Cancer stem cells have several distinct tumorigenic abilities, including stem cell signal transduction, tumorigenicity, metastasis, and resistance to anticancer drugs, which are regulated by genetic or epigenetic changes. Like normal adult stem cells involved in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 161 publications
1
67
0
3
Order By: Relevance
“…Once the regulatory balance is destroyed, uncontrolled CSCs ultimately lead to tumorigenesis. 21 CSCs also transdifferentiate into other multilineage cells to regulate tumorigenesis. 22 Bussolati et al 23 found that renal CSCs differentiated into vascular endothelial cells (ECs) in the bulk of tumors formed in SCID mice after injection of human renal CSCs.…”
Section: The Concept Of Cscs Biological Characteristics Of Cscsmentioning
confidence: 99%
“…Once the regulatory balance is destroyed, uncontrolled CSCs ultimately lead to tumorigenesis. 21 CSCs also transdifferentiate into other multilineage cells to regulate tumorigenesis. 22 Bussolati et al 23 found that renal CSCs differentiated into vascular endothelial cells (ECs) in the bulk of tumors formed in SCID mice after injection of human renal CSCs.…”
Section: The Concept Of Cscs Biological Characteristics Of Cscsmentioning
confidence: 99%
“…Specific gene expression profiles are needed for tumor cell differentiation which are dictated through different signaling pathways, transcription factor activities, as well as epigenetic alterations such as DNA modifications (Jögi, Vaapil, Johansson, & Påhlman, 2012). The involved signaling pathways in CSCs differentiation are BMP (bone morphogenetic protein) and RA (retinoic acid) pathways, while CSCs stemness signaling cascades include JAK/ STAT, Wnt/β-catenin, Hedgehog, Notch, PI3K/PTEN, and NF-kB (Jin et al, 2017;Matsui, 2016). The expression profile of differentiation-associated genes is heterogeneous in nearly all types of tumor cells, probably due to the transcriptional activity of a small population of CSCs in combination with numerous partially differentiated cells (Palmer, Schmid, Berger, & Kohane, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The expression profile of differentiation-associated genes is heterogeneous in nearly all types of tumor cells, probably due to the transcriptional activity of a small population of CSCs in combination with numerous partially differentiated cells (Palmer, Schmid, Berger, & Kohane, 2012). Inhibition of differentiation happens through highly expressed ID (Inhibitor of DNA-binding/ differentiation) proteins as regulators of cell fate (Jin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(all-trans-retinoic acid) and its analogs, HDACI, miR-100, tyrosine kinase, and signal pathways inhibitors can induce CSCs into differentiated cancer cells which could be treated with anti-cancer agents. In addition, to increase sensitivity to cancer treatment, differentiation of CSCs can decrease motility and tumorigenicity of CSCs, and reduce invasion and migration of tumor [41][42][43][44].…”
Section: Induction Of Cscs Differentiation By Agents Like Atramentioning
confidence: 99%